Implementasi Kurikulum Merdeka Belajar di Sekolah Dasar: Dari Teori ke Praktis - Pance Mariati; Mustofa Mustofa (Indonesia Berdaya, 2023)
Maarif NU Educational Institution of Surabaya City houses several schools and there are still many teachers who do not understand theoretically and practically the policy of freedom of learning, even though the teacher's understanding of curriculum reform is very essential. Teachers find it difficult to implement a policy of fredom of learning at school and in the classroom. Teachers have difficulty in developing learning methods referring to independent learning. In addition, teachers have difficulty developing an fredom of learning curriculum (just curriculum transmitter). We provide training and mentoring to teachers for three meetings intensively. The result is an increase in teacher understanding in three aspects; (1), theoretically, (2), how to implement it, and (3), how to develop curriculum. This means that training and mentoring is very important to be carried out by more competent experts. This is in line with the research by Postholm (2012), which states that it is important for teacher training to be carried out by more competent people to increase teachers' understanding of the curriculum.Abstrak: Lembaga Pendidikan Maarif NU Kota Surabaya menaungi beberapa sekolah. Namun sumber daya manusia yang dimiliki masih terbatas serta fasilitas yang dimiliki juga masih relatif terbatas. Masih banyak guru yang belum memahami secara teoretis dan praktis kebijakan merdeka belajar padahal pemahaman guru terhadap reformasi kurikulum sangat esensial. Guru merasa kesulitan menerapkan kebijakan merdeka belajar di sekolah dan di kelas. Guru kesulitan dalam mengembangkan metode pembelajaran merujuk pada merdeka belajar. Selain itu guru kesulitan mengembangkan kurikulum merdeka belajar (curriculum transmitter). Kami memberikan pelatihan dan pendampingan kepada guru-guru selama tiga kali pertemuan dengan intensif. Hasilnya terjadi peningkatan pemahaman guru dalam tiga aspek; (1), secara teoretis, (2), bagaimana mengimplementasikannya, dan (3), bagaimana mengembangkan kurikulum. Artinya pelatihan dan pendampingan sangat penting dilakukan oleh para ahli yang lebih kompeten. Ini selaras dengan penelitian  Postholm (2012), yang menyatakan bahwa pelatihan kepada guru penting dilakukan oleh orang yang lebih kompeten untuk peningkatan pemahaman guru terhadap kurikulum